EFEKTIVITAS PENGGUNAAN MULTIMEDIA PEMBELAJARAN MODEL TUTORIAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Restu Wibawa (Jurnal Paedagogy, 2017)
The purpose of this study was to determine the effect of the use of multimedia learning on the motivation to learn ICT in Class X Students at Madrasah Aliyah Nurul Hakim Kediri. The data collection methods used in this study were questionnaires and documentation. While the data analysis technique uses statistical analysis techniques using the Chi Square formula. From the results of the study based on degrees of freedom (dk) = 9 with a significant level of 5%, the amount of the chi square table is 16.91. In fact, it shows that the calculated chi squared (X²) obtained in this study is greater than the chi square (X²) in the table (17.19> 16.91), this means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha ) received. It means that there is a significant influence between the use of multimedia tutorial model learning on the motivation to learn ICT class X students at Madrasah Aliyah Nurul Hakim Kediri.